Information security - Osman, Amin (Faculty of Information Technology, 2024)
E-commerce: Involves the exchange of money for goods and services over electronic networks and encompasses many of an organization’s outward facing processes—such as sales, marketing, order taking, delivery, procurement of goods and services, and customer service—that touch customers, suppliers, and other business partners. Mobile commerce (m-commerce): is the buying and selling of goods and/or services using a mobile device, such as a tablet, smartphone, or other portable device.
E-commerce and M-commerce